Phrenic nerve transfer to the musculocutaneous nerve for the repair of brachial plexus injury: electrophysiological characteristics - Liu, Ying (Neural Regen Res, 2015)
Phrenic nerve transfer is a major dynamic treatment used to repair brachial plexus root avulsion. We analyzed 72 relevant articles on phrenic nerve transfer to repair injured brachial plexus that were indexed by Science Citation Index. The keywords searched were brachial plexus injury, phrenic nerve, repair, surgery, protection, nerve transfer, and nerve graft. In addition, we performed neurophysiological analysis of the preoperative condition and prognosis of 10 patients undergoing ipsilateral phrenic nerve transfer to the musculocutaneous nerve in our hospital from 2008 to 201 3 and observed the electromyograms of the biceps brachii and motor conduction function of the musculocutaneous nerve. Clinically, approximately 28% of patients had brachial plexus injury combined with phrenic nerve injury, and injured phrenic nerve cannot be used as a nerve graft. After phrenic nerve transfer to the musculocutaneous nerve, the regenerated potentials first appeared at 3 months. Recovery of motor unit action potential occurred 6 months later and became more apparent at 12 months. The percent of patients recovering ‘excellent’ and ‘good’ muscle strength in the biceps brachii was 80% after 18 months. At 12 months after surgery, motor nerve conduction potential appeared in the musculocutaneous nerve in seven cases. These data suggest that preoperative evaluation of phrenic nerve function may help identify the most appropriate nerve graft in patients with an injured brachial plexus. The functional recovery of a transplanted nerve can be dynamically observed after the surgery.